“Good People with Good Intentions”: Deconstructing A Post-Secondary Institution’s Sexual Violence Policy Construction - Shankar, Irene; Tavcer, D. Scharie (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
This exploratory study investigates the bodies tasked with constructing sexual violence policies within a post-secondary institution (PSI). Our findings indicate that allocated committees prioritize institutional risk management, normalize confusion, and most members have little or no understanding of the intersectionality of violence. These findings contextualize PSI's failure to address structural violence.  Our recommendations urge PSIs to include subject experts, consult with existing service providers, and integrate research on the intersectionality of sexualized violence within their policy and program construction.